2023
DOI: 10.15835/nbha51113080
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of commercial quality and bioactive compounds of guava pieces by application of an alginate-acemannan coating

Abstract: The objective of this study was to evaluate the effect of an edible coating based on alginate and acemannan on the commercial quality and concentration of bioactive compounds of guava pieces stored in refrigeration. Pieces of guava were coated with an alginate film enriched with acemannan (A-Ac), with samples without cover used as a control. The fruit pieces with and without the A-Ac coating were stored for 12 days at 6 ± 2 °C. Analyses of colour, firmness, ethylene production, ascorbic acid, total polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…This was because the Ca 2+ in AC increased the network stability favored by the physical interaction with ALG and promoted its gelation and formation of egg-box conformation. Moreover, in the food industry, the application of AC and ALG coatings can increase the ascorbic acid content and antioxidant potential of fruits and preserve their sensory, nutritional, and functional properties, providing new ideas for their future use in the fields of medicine and cosmetics [ 123 ]. In addition, it was found that AC was combined with CS and ALG via the use of electrospinning technology to build a multicomponent system.…”
Section: Combined Application Of Ac and Other Compoundsmentioning
confidence: 99%
“…This was because the Ca 2+ in AC increased the network stability favored by the physical interaction with ALG and promoted its gelation and formation of egg-box conformation. Moreover, in the food industry, the application of AC and ALG coatings can increase the ascorbic acid content and antioxidant potential of fruits and preserve their sensory, nutritional, and functional properties, providing new ideas for their future use in the fields of medicine and cosmetics [ 123 ]. In addition, it was found that AC was combined with CS and ALG via the use of electrospinning technology to build a multicomponent system.…”
Section: Combined Application Of Ac and Other Compoundsmentioning
confidence: 99%